"Contra tudo isso que está aí": como a construção do marketing político e eleitoral do RenovaBR levou Alessandro Vieira ao Senado por Sergipe - Santos, Débora Andrade Barroso (2022)
The present text aims to discuss the aspects that induce, in the 2018 elections, the police chief Alessandro Vieira (currently MDB) to the position of senator for Sergipe, an aspirant without political background or familiar name by the Sergipe population that would legitimize him as a spokesperson. The research is defined from the perspective of the application of RenovaBR's political and electoral marketing tactics in the campaign of Alessandro Vieira, who was a student of the first class of the non-partisan movement in question, in addition to the function of advertising and propaganda, according to the EPC in this context. The reading starts from the political situation between 2013 and 2018 in Brazil, with a brief historical overview of the return of representative democracy in the country; passing through the indispensability of the marketer and his multidisciplinary team for the production of content and dissemination of the candidacy to voters, through Information and Communication Technologies (ICT), making a figure capable of meeting the desires of a large portion of the voting population of the state of Sergipe. Finally, the posts of the candidate's Instagram feed will be analyzed, given the lack of time in the electoral schedule on radio and TV, in order to seek how the strategy was thought, until the construction of the hero's journey, samples of elements that make up the entire convincing narrative used between August 16th and October 6th. The importance of this analysis is given in realizing how new political personas can unite old political practices, disguised as newness, to win the trust of voters; all this using marketing resources on online and offline media platforms, bringing to light the subjectivity of social aspirations among of a social, political and economic “crisis of representation”.